Symmetric expressions of order 2n with essential spectrum and deficiency index greater than n - Limson, Gabriel Enrique H.
For arbitrary n ∈ N, it shall be shown that there exist real symmetric diﬀerential expresssions of order 2n which have non-empty essential spectrum and are not in the limit point case. In particular we give an explicit form for a diﬀerential expression M such that d(M)= n + 1 and another form such d(M)= n + 2.